Requirements Elicitation Challenges and Strategies for GSD Based Projects (Pakistan Journal of Scientific Research, 2021)
The  geographically  distributed   software  development  has  attained   a  significant  attraction  in software  development industry  since last few decades due to its wide acceptance across the globe. The main essence of geographically distributed  software development is to expand  company working by follow-the-sun  strategy,  get  skilled  labors  at  cheaper   rates  from  low  economy  regions  of  world  and  pool-up  company resources  to raise their utilization  graph.  The requirements elicitation process is considered  as one of the most challenging tasks  during  software  development  process  in  traditional as  well as geographically distributed software development projects due to its social and collaborative  nature. This article presents a comprehensive insight about major challenges faced by requirements elicitation teams engaged in geographically distributed software development projects.  The article also elaborates the possible strategies, which can be adopted to minimize the negative impact of geological distribution of software development activities. The presented study will help the requirements elicitation teams to better plane their requirements elicitation sessions for geological distributed software development projects by encountering the expected hurdles.
Keywords: Requirements Elicitation; Requirements Elicitation in GSD; Requirements Elicitation Challenges; Distributed Requirements Elicitation; Distributed Software Development